Social Phenomenology of Kensiu Indigenous People - Nur Faaizah Md Adam; Md Noor Saper; Ciptro Handrianto; Shahid Rasool (International Journal of Education, Information Technology, and Others, 2022)
This research aims to find out how the religious system and beliefs of the Kensiu Indigenous People relate to the art system in the Kensiu Indigenous People. This research uses a type of qualitative research using a phenomenological approach, an in-depth research approach to reveal problems based on phenomena and events. Results The religious system or belief and art are closely interrelated; in every community ritual, there is also an art that complements it. In the religious system of the Kensiu indigenous people's beliefs, in terms of the beliefs of the Indigenous People in general, they still practice the faith of animism, in which they believe that all things and creatures have a spirit. The belief system of the Indigenous People, in general, is seen to be disappearing and being eroded due to the current modernization and globalization that is happening today. This small number of Kensiu speakers can also wipe out the culture passed down from generation to generation.